A educação a distância no desenvolvimento de competência em informação em bibliotecas universitárias: estudo de caso na biblioteca da Universidade Federal de Alagoas, campus Arapiraca - Albuquerque, Márcio Thiago dos Santos (2020)
Advances in the popularity of Digital Technologies of Information and Communication (DTIC)– mainly through the internet, – have resulted in an increasing availability of information if compared to the capacity of production of traditional paper based supports. However, this informational boom has demanded that users put to practice their capabilities of checking and validating the searched information, which has been considered a modern challenge. In the educational context, it is possible to develop strategies that help to face this reality. Hence, the present research aims to map the difficulties related to information searching faced by the students of the Federal University of Alagoas Campus Arapiraca that usually use the campus’ library. It has the purpose of developing pedagogical strategies by means of Distance Learning in order to fill gaps related to the process of search and usage of the information. The present research is developed in a quali/quantitative approach, of applied nature and corresponds to the modality of field search, Case Study. The library presented in the Campus Arapiraca was taken as subject for this research using four types of samplings throughout this study. In all of them it was performed the sampling technique of accessibility and convenience. Tools such as questionnaires, interviews and focal groups were used. Considering that this constitutes a professional master’s research in Science of Information, its informational products is presented in the form of a introductory course for the training and capacitation of users of the Campus Arapiraca library in the modality of Distance Learning. It is concluded that the presented course brought real improvements to the daily activities of students in regard to the search and usage of scientific information.